(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Background: Few studies have examined individual transitions in smoking status in national populations. Methods: A representative sample of 21,970 men and women aged 15-64 were questioned regarding current smoking status and smoking status of 12 months ago. Results: 1.6% of respondents had started to smoke and 1.6% had quit smoking. Becoming a smoker was significantly associated with younger age and lower social economic status (SES). Among women, many new smokers were between the age of 30 and 34, presumably due to relapse after pregnancy. High SES smokers quit at a younger age than lower SES groups. Conclusion: To reduce smoking prevalence in the Netherlands, more attention should be given to women aged 30-34 years and to people from the lower SES groups, especially those under the age of 45. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 90-93